Evaluating dose response lysolecithin supplementation on growth, antioxidant response, and immunity in giant river prawn Macrobrachium rosenbergii - Qiu, Zongsheng; Xu, Qiyou; Chong, Chou Min; de Cruz, Clement R. (Elsevier B.V., 2025)
This study evaluated the effects of dietary lysolecithin (LL) supplementation on growth performance, body composition, biochemical responses, antioxidant capacity, digestive enzyme activity, histological study, and disease resistance in Macrobrachium rosenbergii. Six isonitrogenous and isocaloric diets were prepared for the dose-response trial by supplementing LL to the basal diet at six graded levels (0 g/kg, 2 g/kg, 4 g/kg, 6 g/kg, 8 g/kg, and 10 g/kg of dry weight) while propotionally reducing fish oil content. The prawns were fed for 56 days, after which various physiological and biochemical parameters were assessed. The results showed that dietary LL significantly increased final body weight, weight gain, and specific growth rate, with the optimal inclusion level estimated at 4.8 g/kg based on a second-order polynomial regression model. Additionally, LL supplementation increased superoxide dismutase activity and glutathione levels while reducing malondialdehyde levels. LL also improved digestive enzyme activities, reduced lipid accumulation in the hepatopancreas, lowered hemolymph triglyceride levels, and enhanced intestinal amylase and trypsin activities. Furthermore, prawns fed with diets containing 4–10 g/kg LL exhibited significantly reduced cumulative mortality following a challenge with Aeromonas hydrophila. To conclude, these findings demonstrated that dietary LL regulates metabolism, improves growth performance, antioxidant capacity, digestive function, hepatopancreatic health, and disease resistance in Macrobrachium rosenbergii, with an optimal recommended inclusion level estimated at 4.8 g/kg based on quadratic regression analysis.